2017
DOI: 10.1038/srep41356
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic flux, a possible mechanism for delayed gentamicin-induced ototoxicity

Abstract: Aminoglycoside antibiotics including gentamicin (GM) induce delayed ototoxic effects such as hearing loss after long-term use, unlike the early-onset ototoxicity caused by cisplatin. The purpose of the study was to identify the mechanism of the delayed GM-induced ototoxicity by exploring the role of autophagy in vitro and in vivo. Treating HEI-OC1 auditory cells with GM led to a time-dependent increase of the autophagosome marker LC3-II, which was accompanied by cell death. In contrast, cisplatin and penicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 44 publications
2
24
0
1
Order By: Relevance
“…Recent reports have shown that aminoglycoside antibiotics induce autophagy when injected i.p. in rats (46). However, the basal levels of autophagy were very low in the cochleae, since little LC3II was detected.…”
Section: μM (D-f) (G)mentioning
confidence: 90%
“…Recent reports have shown that aminoglycoside antibiotics induce autophagy when injected i.p. in rats (46). However, the basal levels of autophagy were very low in the cochleae, since little LC3II was detected.…”
Section: μM (D-f) (G)mentioning
confidence: 90%
“…Recent studies showed that gentamicin-mediated ototoxicity was closely associated with impairment of autophagy. Gentamicin was demonstrated to impair the fusion of autophagosome and lysosome, which led to a time-dependent increase of autophagosome marker LC3b-II, and subsequently an increase of cell death [Kim et al, 2017]. Independent studies also showed that activation of autophagy was able to attenuate gentamicin-induced ototoxicity and nephrotoxicity [Cui et al, 2015;He et al, 2017].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that gentamicin-mediated ototoxicity was associated with impairment of autophagic flux [Kim et al, 2017]. To study if the same mechanism applied to synergistic ototoxicity from gentamicin and low-dose irradiation, we monitored the protein level changes of LC3b-I and II (components of the autophagosome) and SQSTM1/p62 protein (a substrate of autophagy) in cells exposed to gentamicin, radiation, or both.…”
Section: Perturbation Of Autophagic Flux Was Detected In Cells Exposementioning
confidence: 99%
“…Blocking autophagy flux by AG results in the accumulation of autophagosome bodies, resulting in ear toxicity. By contrast, enhancement of autophagic flux is believed to improve AG-induced [54] and cisplatin-induced [55] auditory cell death. The antioxidant aspect of autophagy also acts as an important defense mechanism for other types of acquired hearing loss, such as noise-induced and age-related hearing loss.…”
Section: Discussionmentioning
confidence: 99%